On Being an Unhomely Other - Ahmad, Misbah (Satura, 2022)
I had eyes staring at me for how I chose to dress, My dress gets stares here too and implies that I am repressed. I was the “other” back at the place I wanted to call my home, I am the “other” in the streets I now occasionally roam.